Pengembangan Strategi Branding dan Optimalisasi Pemasaran Digital pada Kapapah Jaya Catering untuk Meningkatkan Daya Saing UMKM - Dasmen, Rahmat Novrianda; Prasetyo, Abdi; Amelia, Astreet; Kartika, Entarisa Asma; Hesti; Anggraini, Tania (MAYARA: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to develop branding strategies and optimize digital marketing for Kapapah Jaya Catering, an SME in Palembang, in order to increase competitiveness. The activity was carried out through the Merdeka Belajar Kampus Merdeka (MBKM) internship program for 4 months (October 2024–January 2025), involving 5 students from various study programs. The method used was Participatory Action Research (PAR), which included situation analysis, participatory observation, in-depth interviews, and work program implementation. The work program implemented included visual identity redesign (rebranding), social media content optimization, product packaging design innovation, and the implementation of a Corporate Social Responsibility (CSR) program in the form of sharing activities in the surrounding environment. The results of the activity showed the creation of a new logo and consistent visual identity (color palette and font), which improved the professional image of the SMEs. This activity provided tangible benefits in the form of increased brand visibility and competitiveness of SMEs in the digital culinary market, while also proving that academic-business collaboration can be a concrete solution to the challenges of SME digitalization.